Acoustic stridulating responses of various tarantula species in Peninsular Malaysia - Irham Razak; Dzulhelmi Muhammad Nasir; Amirrudin Ahmad (Penerbit Universiti Kebangsaan Malaysia, 2024)
Stridulation by stridulatory organs has been linked to tarantulas’ (Araneae: Theraphosidae) defence or sexual communication, and the morphology of such organ has been extensively used in tarantula systematics. This study was conducted to characterise and compare differences in the acoustic pattern of stridulating sound among seven tarantula species for juveniles and adults of both sexes in Peninsular Malaysia. The species were Psednocnemis jeremyhuffi, P. brachyramosa, Selenocosmia sp. ‘Johor’, Omothymus violaceopes, Cyriopagopus robustus, Chilobrachys sp. ‘Kedah’, and Coremiocnemis sp. ‘Kelantan’. Five provocation methods were used to record the sound which was by tapping the substrate/enclosure, blowing air, waving a pen, poking with blunt object and shaking the enclosure. The stridulating behaviour was assessed using a set of parameters. The result showed that the stridulating behaviour differed between species. Dwarf species like P. jeremyhuffi and P. brachyramosa did not make any audible stridulating sound and preferred to remain motionless. Meanwhile, for the other five species only the large adult females stridulated. Adult males of all species did not make any audible sounds, but rather appeared to be more aggressive and frequently bite. Kruskal-Wallis test showed that intensity, pitch frequency, call duration and pulse duration were significantly different between species. Principal component analaysis (PCA) showed the dissimilarity between the adult females from the five species with Omothymus violaceopes and Chilobrachys sp. ‘Kedah’ the most distinct in terms of call patterns. This study provides evidence on the acoustics pattern of stridulating sound for the tarantulas in Peninsular Malaysia.